2016
DOI: 10.1111/1742-6723.12696
|View full text |Cite
|
Sign up to set email alerts
|

Blood cultures and bacteraemia in an Australian emergency department: Evaluating a predictive rule to guide collection and their clinical impact

Abstract: Bacteraemia detected in the ED alters subsequent patient management. The predictive rule can be safely applied in the ED to determine need for blood culture collection. Blood cultures should not be omitted in the ED based entirely on preliminary diagnosis given the high discordance seen between ED and discharge diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
5
1
1
Order By: Relevance
“…In Asia, the incidence rate of multidrug-resistant and hypervirulent Klebsiella pneumoniae strains increased. 15 We found that there were 3 patients with carbapenem resistance; however, the patients were not included in our study because of the surgery and the discontinued visiting of the patients.…”
Section: Discussionmentioning
confidence: 90%
“…In Asia, the incidence rate of multidrug-resistant and hypervirulent Klebsiella pneumoniae strains increased. 15 We found that there were 3 patients with carbapenem resistance; however, the patients were not included in our study because of the surgery and the discontinued visiting of the patients.…”
Section: Discussionmentioning
confidence: 90%
“…Bacteria could be identified in 11 (69%) cases, 8 (50%) of which were positive for Klebsiella pneumoniae . In Asia, the incidence rate of multidrug-resistant and hypervirulent Klebsiella pneumoniae strains increased [ 15 ]. We found that there were 3 patients with carbapenem resistance; however, the patients were not included in our study because of the surgery and the discontinued visiting of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the rapid progression of the disease, and lack of a standardized antibiotic treatment strategy for endogenous endophthalmitis, it is difficult to obtain this condition, and the results of the culture may be unreliable. 12 Therefore, for effective management of endogenous endophthalmitis, blood samples should be collected before starting antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%